Implementation of the MDLC Method in the Development of Android-Based Augmented Reality for Traditional House Recognition - Am, Andri Nofiar; Pribadi, Antoni; Nurkholis, Nurkholis; Perdana, M.Alkadri; Rukhshah, Muhammad (Internet of Things and Artificial Intelligence Journal, 2025)
Indonesia has a rich cultural diversity, one of which is traditional houses (rumah adat). However, learning about traditional houses is still largely based on textbooks. With the advancement of information and communication technology, teaching and learning processes can now be supported by interactive learning media. One of the emerging technologies that is widely used in education is Augmented Reality (AR). AR can display 3D animations from all angles, helping to increase public interest in learning more about Indonesia’s diverse traditional houses. The purpose of this research is to develop an Android-based Augmented Reality application for introducing traditional houses in Indonesia as a learning medium. This application aims to provide users convenience in learning, and seeing various types of houses there. The method used is the Multimedia Development Life Cycle (MDLC) which consists of a concept, design, collection of materials, assembly process, testing process, and distribution process. The application uses Unity, Blender, and Vuforia SDK. The results of this study will show that the Android-based Augmented Reality (AR) marker application, specifically the traditional houses in Indonesia. 3D assets of traditional houses can be adjusted flexibly, for example, rotated by 360 degrees, accompanied by descriptive information on each traditional house, so that information can be received flexibly and real-like.